2023
DOI: 10.3389/fpls.2023.1150854
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS-based metabolomics approach identified novel antioxidant flavonoids associated with drought tolerance in citrus species

Abstract: Citrus fruits are cultivated around the world, and they face drought stress frequently during their growth and development. Previous studies showed that citrus plants biosynthesized flavonoid compounds in response to abiotic stress. In this study, we have quantified 37 flavonoid compounds from the leaves of three distinct citrus species including sour orange (drought-tolerant), pummelo ‘Majia you pummelo’ (drought-sensitive), and lemon (drought-sensitive). The 37 flavonoids consisted of 12 flavones, 10 flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Vitexin shows various biological activities, including antioxidant, anticancer, and anti-inflammatory activities [32,33]. Choline is an essential nutrient for liver, muscle, and brain function, and both choline and choline alfoscerate have been shown to have anti-Alzheimer activity [9,34]. These findings suggest that hemp seeds from the Bama region provide various health benefits, and this might contribute to the good physical health of the local people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitexin shows various biological activities, including antioxidant, anticancer, and anti-inflammatory activities [32,33]. Choline is an essential nutrient for liver, muscle, and brain function, and both choline and choline alfoscerate have been shown to have anti-Alzheimer activity [9,34]. These findings suggest that hemp seeds from the Bama region provide various health benefits, and this might contribute to the good physical health of the local people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hemp seeds are rich in flavonoid metabolites [5,8]. Flavonoids also exhibit diverse biological activities, including anticancer, antidiabetic, antiviral, anti-heart disease, antimicrobial, antioxidant, and anti-Alzheimer activities, and have been shown to promote the homeostasis of the intestinal flora [9][10][11][12][13][14][15]. The oil of hemp seeds also provides various health benefits; previous studies have shown that it contains more polyunsaturated fatty acids and rare fatty acids, such as γ-linolenic acid and stearidonic acid, compared with other cooking oils [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the soil water content and sunlight exposure affected the secondary metabolite profile and volatile compound levels of white grapes [38], quince [18], and grape berry [39]. A low soil water content causes drought and salt stress in citrus plants, resulting in reduced plant growth and leaf area, which ultimately affects photosynthesis, respiration, and metabolite profiles [40][41][42]. Moderate drought stress decreases the content of citric and malic acids in fruits such as nectarines [43] and grapes [44], which is in line with our results (Figure 3), whereas the opposite was reported for ponkan fruits grown in soil with 40% maximum water capacity under water stress [45].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, flavonoid and phenolic acid concentrations were little affected in the leaves of Amaranthus cruentus L. when water was withheld from greenhouse-cultivated plants for 6 days [ 31 ]. Moreover, Rao et al [ 32 ] determined that a greater proportion of leaf flavonoid constituents were elevated in a drought-tolerant sour orange and to a higher magnitude after 18 days of drought, whereas fewer metabolites were impacted in the leaves of a drought-sensitive lemon. Thus, there appears to be a discrepancy as to whether phenylpropanoids accumulate with drought.…”
Section: Introductionmentioning
confidence: 99%